Kaposi sarcoma in people living with HIV: incidence and associated factors in a French cohort between 2010 and 2015. (15th March 2020) - Poizot-Martin, Isabelle; Lions, Caroline; Cheret, Antoine; Rey, David; Duvivier, Claudine; Jacomet, Christine; Allavena, Clotilde; Huleux, Thomas; Bani-Sadr, Firouze; Obry-Roguet, Véronique; Makinson, Alain
Abstract : Objective: Kaposi sarcoma is still observed among people living with HIV (PLHIV) including those on ART with undetectable HIV viral load (HIV-VL). We aimed to assess Kaposi sarcoma incidence and trends between 2010 and 2015 in France and to highlight associated factors. Design: Retrospective study using longitudinal data from the Dat'AIDS cohort including 44 642 PLWH. For the incidence assessment, Kaposi sarcoma cases occurring within 30 days of cohort enrollment were excluded. Methods: Demographic, immunological, and therapeutic characteristics collected at time of Kaposi sarcoma diagnosis or at last visit for patients without Kaposi sarcoma. Results: Among 180 216.4 person-years, Kaposi sarcoma incidence was 76 (95% CI 64.3–89.9)/10 5 person-years. Multivariate analysis (Poisson regression) revealed the positive association with male sex, MSM transmission route, lower CD4 + T-cell count, higher CD8 + T-cell count, not to be on ART, whereas HIV follow-up time, duration with an HIV-VL 50 copies/ml or less were negatively associated with Kaposi sarcoma. According to the different models tested, HIV-VL, CD4 +  : CD8 + ratio and nadir CD4 + cell count were associated with Kaposi sarcoma. Moreover, stratified analysis showed that patients with a CD4 +  : CD8 + ratio 0.5 or less or a CD8 + T-cell count greater than 1000 cells/μl were at higher risk of Kaposi sarcoma regardless of the CD4 + T-cell count. Conclusion: This study showed that in a resource-rich country setting with high ART coverage, Kaposi sarcoma still occurred among PLWH. CD8 + hyperlymphocytosis and CD4 +  : CD8 + ratio should be now considered as two useful markers to better identify patients at increased Kaposi sarcoma risk, including those with a CD4 + T-cell count greater than 500 cells/μl.